(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2005)
The service purchaser needs to stipulate for the service. The service contributor will afford the service to the purchaser.The powerful use of services to assemble business processes in service computing pressures that the Quality of Services (QoS) convene consumersâ€™ perspective. When Â manipulating the services, a service provider must Â set apart the quality of service levels that will be existing to the Â customers. Programmed web-based negotiation of Service Level Agreements (SLA) can assist in describing the QoS necessities of critical service-based processes. We put forward a trusted Negotiation Organizer(NO) structure that performs adaptive and intelligent mutual bargaining of SLAs between a service contributor and a service purchaser based on each partyâ€™s elevated level business necessities. We also define an algorithm for adapting the decision functions during an continuing negotiation to match with an opponentâ€™s offers or with simplified purchaser preferences. The NO uses intelligent agents to conduct the negotiation locally by choosing the most suitable multi criteria decision making system known as Analytic Hierarchy Process (AHP).